Immunohistochemical Coexpression of VEGF and CD34 in Ameloblastoma - Younis, Wasan H.; Garib, Balkees T.; Hussein, Ala’a G. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Angiogenic potential m most tumors; characterized by VEGF and vascular bed density around tumor islands, is believed to be an important marker in predicting tumor growth, recurrence and metastasis. Materials and Methods: The study included 50 cases of ameloblastomas. From each case 4 μm sections were stained IHC with antivascular endothelial growth factor antibody- and endothelial lined vessels anti CD34 antibody to evaluate their expression and intensity in relation to their Fac Med Baghdad clinicopathological features. Results: Generally, VEGF was significantly highly expressed with strong intensity in outer cell layer of tumor islands, and the newly formed blood vessels were significantly predominantly rounded and small in size in comparison to dental folicale and papilla of tooth germ. Young aged patients (≤ 20yrs) had highest mean MvD around tumor islands (35.9). Regarding WHO classification; follicular, plexiform and lining cells in UAB had higher expression then acanthomatous and types, but 67% of those in plexiform were of moderate intensity. There was no significant differences in mean MvD in all histological solid subtypes, and characterized by round and small vessels. Except those in plexiform, they were elongated and medium. UAB had significant lower microvessel count around lining tumor cells (but not around mural growth) and more percentage of elongated medium sized vessels than follicular but less than plexiform. There was significant correlation between VEGF expression and the shape of microvessels. Considering different morphological cellular pattern, basal cells showed the highest VEGF positivity and intensity (87.5). Conclusions: The present study indicate the usefulness of the VEGF expression and MvD in explaining the aggressive, locally invasive biological behavior of ameloblastoma. The high angiogenic potential is enhancing tumor cell survival and the increase in the production of new blood vessels formation is facilitating tumor growth, and by time will enhance the proliferation potential of the incompletely removed surviving tumor islands, so increasing the chance of ameloblastoma recurrence.